PENINGKATAN PENGETAHUAN TENTANG PENGGUNAAN DAN PENGELOLAAN OBAT YANG RASIONAL MELALUI PENYULUHAN DAGUSIBU KEPADA DISABILITAS TULI: Increasing Knowledge About Rational Use And Management Of Medications Through Dagusibu Counseling For Deaf Disabilities - Istianah Purnamasari; Yuyun Sri Wahyuni; Basir, Hernawati; Muthmainnah Thalib; Sulaiman; Ainun Jariah; Sri Widyastuti; Muhammad Taufik Duppa; Anshari Masri; Andri Anugerah Pratama (Akademi Farmasi Yamasi Makassar, 2023)
Knowledge about treatment should be known by all people, including the deaf community. The increase in self-medication by people can result in the risk of using the wrong medication and irrational therapy if they are not equipped with adequate knowledge. The high rate of self-medication in the community is due to the lack of public knowledge regarding the proper and correct use of medicines.lack of information obtained from health workers, as well as a lack of public awareness and ability to seek information through available information sources.The DAGUSIBU program exists as an effort to increase public knowledge in using and managing drugs. This service activity aims to determine the difference in changes in knowledge before and after counseling. The method used is a quantitative method with designquasi experimental with one group pre and post test design with methodactive and participatory learning. Increasing knowledge about the rational use and management of medicines through Dagusibu counseling for the deaf and disabled community has been carried out well, the total number of participants was 44 people consisting of men and women with the highest age group being 30-50 years.61,36 %, Average Education LevelSMP (40%) or as many as 18 people. The extension activities carried out have increased participants' knowledge from previously 4.55% and after the activity it increased to 45.45%.